2012
DOI: 10.1152/japplphysiol.01293.2011
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of corticosteroid treatment on airway inflammation, mechanics, and hyperpolarized 3He magnetic resonance imaging in an allergic mouse model

Abstract: The purpose of this study was to assess the effects of corticosteroid therapy on a murine model of allergic asthma using hyperpolarized (3)He magnetic resonance imaging (MRI) and respiratory mechanics measurements before, during, and after methacholine (MCh) challenge. Three groups of mice were prepared, consisting of ovalbumin sensitized/ovalbumin challenged (Ova/Ova, n = 5), Ova/Ova challenged but treated with the corticosteroid dexamethasone (Ova/Ova+Dex, n = 3), and ovalbumin-sensitized/saline-challenged (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…A majority of these defects remained persistent with time and with repeated bronchoconstriction [ 25 , 26 ]. Since then, there have been a number of advancements in HP 3 He-MRI with the emergence of quantitative methods to extract detailed structure-to-function relationships in asthma in both humans [ 23 , 24 , 30 , 32 ] and animals [ 40 43 ]. For example, recent efforts have calculated a characteristic index to quantify the degree of ventilation heterogeneity [ 23 , 30 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A majority of these defects remained persistent with time and with repeated bronchoconstriction [ 25 , 26 ]. Since then, there have been a number of advancements in HP 3 He-MRI with the emergence of quantitative methods to extract detailed structure-to-function relationships in asthma in both humans [ 23 , 24 , 30 , 32 ] and animals [ 40 43 ]. For example, recent efforts have calculated a characteristic index to quantify the degree of ventilation heterogeneity [ 23 , 30 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently emerging non-invasive imaging technologies such as magnetic resonance imaging (MRI), micro-CT and optical imaging have been applied to longitudinal monitoring of airway remodeling and inflammation in murine models [ 11 14 ]. The clinical imaging system used in MRI, CT and PET, have been further adapted to murine models of asthma [ 11 , 15 17 ], to serve as a preclinical and translational step between basic discovery and clinical practice, whereas optical imaging technologies developed in experimental settings may also slow-down their way into the clinical practice, especially in the context of intraoperative activities [ 18 , 19 ]. Recently a mouse model transiently expressing the luciferase reporter gene under the control of a bovine IL-8 promoter has been generated [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to homogeneous airway behavior during bronchoconstriction, imaging studies have demonstrated the emergence of VDefs in humans [1][2][3][4][35][36][37] and in animals [38][39][40]. VDefs are direct evidence for major regional differences in ventilation, airflow and parenchymal tidal expansion, which has implications for the peak transmural pressure of the airways: (1) the increase in regional tidal expansion leads to substantially higher peak transmural pressures compared to conditions with the relaxed airways, homogeneous ventilation distribution and quiet tidal breathing, and (2) increased airway resistance as well as its heterogeneity affects the intraluminal pressures in the bronchial tree.…”
Section: Discussionmentioning
confidence: 99%